Médiation au design avec des ingénieurs : le tact comme posture - Dorian Reunkrilerk (Société Française de Sciences de l’Information et de la Communication, 2021)
Innovation as an injunction prompts organizations to adopt replicable and transferable practices. In this context, design thinking is used as a toolbox that can be appropriated by non-designers, to the detriment of the cognitive attitudes and states of mind associated with a Design culture, as well as to the detriment of preexisting company cultures. This study draws on action research carried out within a multinational metalworking industry. It aims at understanding what emerges when two sometimes dissonant design and engineering cultures come together. We propose to analyze such dialogue, the postures of the individuals involved, and the potential transformative effects, through the notion of tact. We thus intend to show how a situation of mediation, equipped by intermediary objects, deploys in a twofold way. While it acts on the standardization of design practices and their stabilization over time, it can also initiate a redefinition of roles, identities and social dynamics, opening up potential cultural changes in the organization.